1996
DOI: 10.1007/bf00863556
|View full text |Cite
|
Sign up to set email alerts
|

Crop residue effects on surface radiation and energy balance ? review

Abstract: Crop residues alter the surface properties of soils. Both shortwave albedo and longwave emissivity are affected. These are linked to an effect of residue on surface evaporation and water content. Water content influences soil physical properties and surface energy partitioning. In summary, crop residue acts to soil as clothing acts to skin. Compared to bare soil, crop residues can reduce extremes of heat and mass fluxes at the soil surface. Managing crop residues can result in more favorable agronomic soil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
72
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 42 publications
1
72
0
6
Order By: Relevance
“…Previous studies, however, have focused exclusively on the potential impact on the mean climate (7), whereas the influence of this practice on temperature extremes has never to our knowledge been explored. Moreover, crop residue management may also influence climate conditions through changes in evapotranspiration (6), and this effect to our knowledge has so far never been considered.…”
mentioning
confidence: 99%
“…Previous studies, however, have focused exclusively on the potential impact on the mean climate (7), whereas the influence of this practice on temperature extremes has never to our knowledge been explored. Moreover, crop residue management may also influence climate conditions through changes in evapotranspiration (6), and this effect to our knowledge has so far never been considered.…”
mentioning
confidence: 99%
“…This may significantly reduce soil θ and SWS, leaving potentially low antecedent soil water availability to emerging and young cash crop in years when water limiting stress may be high, such as the 2012 drought (Ewing et al 1991;Campbell et al 1984). In contrast, standing or laying vegetation above the soil surface, whether living or dead, raises a field's atmospheric boundary layer, reduces wind speeds at the soil surface, and lowers soil short wave radiation absorption, all resulting in potentially lower soil evaporative losses (McMaster et al 2000;Sauer et al 1996aSauer et al , 1996bHorton et al 1996;Horton 1989;Wagger and Mengel 1988). These phenomena are collectively well known as the mulch effect.…”
mentioning
confidence: 99%
“…Though numerous soil processes contribute to the alteration of soil-surface CO 2 effluxes in compacted soils, the change in soil total porosity and the pore-size distribution is likely the primary contributors (Or and Ghezzehei, 2002;Horn et al, 2000;Ahuja et al, 2000). Another example is given by Horton et al (1996) who reported substantially greater and more widely varying temperatures in soils without residue coverage due to residue effects on surface energy partitioning. Soils lacking surface residues had greater soil water evaporative fluxes due to both the increased heat input and the absence of an additional resistance layer (Horton et al, 1996).…”
mentioning
confidence: 99%
“…Another example is given by Horton et al (1996) who reported substantially greater and more widely varying temperatures in soils without residue coverage due to residue effects on surface energy partitioning. Soils lacking surface residues had greater soil water evaporative fluxes due to both the increased heat input and the absence of an additional resistance layer (Horton et al, 1996). Tillage has been reported to significantly increase soilsurface CO 2 effluxes in the days immediately after tillage as well as when emissions were accumulated across the growing season (Omonode et al, 2007;Reicosky and Lindstrom, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation